Efecto citotóxico del extracto clorofórmico de hojas de Annona cherimola en una línea celular de cáncer de colon humano en medio de cultivo con pH ácido y neutro - Torres Alama, Janneth Consuelo (2016)
Cancer of the colon or rectum is a malignant tumor that develops in the last portion of the digestive tract, the large intestine is made up of the colon and rectum as a result of factors related to lifestyle, diet, weight and the exercise; Scientific studies now provide interesting data on the anticancer effects of plant products such as the Annona cherimola. Faced with the prospect of meeting the beneficial effects of this plant for its anticancer properties, the present research was aimed at determining the cytotoxic effect of Annona cherimola sheets in a cell line of human colon cancer (RKO) in culture media with acid pH and neutral pH, executed in the biotechnology center at the National University of Loja, it is a prospective investigation in which experimental techniques trypsinization, cell proliferation and staining were used trypan blue methods that permitted the observation cytotoxic effect of Annona cherimola plant against abnormal cells in a cell line of human colon cancer. As relevant results regarding cell proliferation was observed that the chloroform extract is more potent at 72 hours incubation 28.5% showing both acidic pH to neutral pH in multiplication of cancer cells and growth; regarding cell viability we can conclude that the chloroform extract concentrated provides increased cytotoxic effect on cells of human colon cancer in acid 75.6% 72.6% pH and neutral pH within 72 hours of incubation. Keywords: cytotoxicity, cell viability. Cell line of colon cancer (RKO), cherimola annona.